2009
DOI: 10.1021/ie900070a
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Ti Species in the Li−Mg−N−H System for Hydrogen Storage: A Theoretical and Experimental Investigation

Abstract: With the properties of the Li-Mg-N-H system improved by the doped Ti species, the activation energies of these systems were estimated by an Arrhenius plot, and this elucidated a slightly decreased value with doped TiF 3 . To explore the nature of Ti species in the Li-Mg-N-H system, the crystal structure of Li 2 MgN 2 H 2 with doped Ti was calculated and determined as Li 7 TiMg 4 (N 2 H 2 ) 4 by a first principle approach. As a result, the Li-N and N-H bonds in Li 7 TiMg 4 (N 2 H 2 ) 4 were markedly weakened, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[18,19] Exceptional adsorptive properties of polysaccharides are mainly attributed to: (i) high hydrophilicity of the polymer due to the hydroxyl groups of glucose units; (ii) the presence of a large number of functional and reactive groups (like acetamido, primary amino, hydroxyls or sulfonates group); and (iii) flexible structure of the polymer chain, [20] and its facile modification. [21] Recent evidence suggests that the extracellular polymeric substance that forms the stalk consists of sulfated polysaccharides, [4] which form complex cross-linked structures (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Exceptional adsorptive properties of polysaccharides are mainly attributed to: (i) high hydrophilicity of the polymer due to the hydroxyl groups of glucose units; (ii) the presence of a large number of functional and reactive groups (like acetamido, primary amino, hydroxyls or sulfonates group); and (iii) flexible structure of the polymer chain, [20] and its facile modification. [21] Recent evidence suggests that the extracellular polymeric substance that forms the stalk consists of sulfated polysaccharides, [4] which form complex cross-linked structures (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…(6) Transition metals have been shown to significantly improve kinetics and reduction of dehydrogenation temperatures in many hydrogen storage systems, including NaAlH 4 [4][5][6][7][8], MgH 2 [9][10][11][12], the 1:1 MgH 2 :LiNH 2 [2,13] and 2:1 LiNH 2 :MgH 2 [14]. Through the electronic structure and total energy calculation using first principle calculations on the effect of titanium on MgH 2 , Song et al found that the bond between magnesium and hydrogen was weakened [15].…”
mentioning
confidence: 99%
“…Lu et al observed an increase in hydrogen absorption kinetics of 1:1 LiNH 2 :MgH 2 with the addition of 4 wt% TiCl 3 resulting in an increase in capacity from 5 wt% to 7.9 wt% [2]. For the 2:1 LiNH 2 :MgH 2 system, through density of states analysis, Wang et al found that the N-H bonds were weakened by a Ti atom substituted by a Li atom and the decreased energy value of Li vacancy formation indicated improvement in rehydrogenation of Li 2 MgN 2 H 2 with Ti additive [14].…”
mentioning
confidence: 99%
“…Chen et al [107] introduced different carbon materials such as single-walled carbon nanotubes (SWNTs), multi-walled carbon tubes (MWNTs), graphite and activated carbon into the Mg(NH 2 ) 2 -2LiH mixture as additives, and found that about 90% of the hydrogen capacity can be released at 200 • C in 20 min from the sample with addition of SWNTs while less than 60% of the hydrogen capacity was released from the pristine sample. In addition, many chemicals, such as NaH, NaNH 2 , TiN, TiF 3 , TaN, Li 3 N, V, V 2 O 5 , VCl 3 , Ti 3 Cr 3 V 4 hydride and graphite-supported Ru nanoparticles were also added as catalysts for improving the kinetics of the Mg(NH 2 ) 2 -2LiH system [108][109][110][111][112][113][114]. But the operating temperatures for hydrogen absorption/desorption are still far from the practical requirement.…”
Section: Tuning On Thermodynamics and Kinetics Of Hydrogen Storage Prmentioning
confidence: 99%